2
$\begingroup$

I have been trying to solve this equation

$$\left( 8y+10x \right) \mathrm{d}x+\left( 5y+7x \right) \mathrm{d}y=0\\ $$

by finding integrating factor, though is there more rational way to do it?

$\endgroup$
  • 3
    $\begingroup$ Hint: Let $$ y = v x \implies y' = v + v' x$$ Now substitute and solve. $\endgroup$ – Moo May 28 '17 at 22:36
  • $\begingroup$ Thank you, that should do it! $\endgroup$ – Jack Nickolson May 28 '17 at 22:39
6
$\begingroup$

Turning Moo's comment into an answer. In general if we have something of the form $$\frac{\mathrm{d}y}{\mathrm{d}x} = -\frac{8y + 10x}{5y + 7x} = -\frac{8\frac{y}{x} + 10}{5\frac{y}{x} + 7}$$ i.e $y' = f(y/x)$ then it is a good idea to try the substitution $y=vx \implies y' = v + v'x$ to get $$v + x\frac{\mathrm{d}v}{\mathrm{d}x}=-\frac{8v+10}{5v +7}\implies x\frac{\mathrm{d}v}{\mathrm{d}x} = -\left(\frac{8v+10}{5v+7} +\frac{5v^2+7v}{5v+7}\right)=-\frac{5(v+2)(v+1)}{5v+7}$$ which is a separable equation $$\int\frac{5v+7}{5(v+2)(v+1)}\, \mathrm{d}v=-\log x + c \implies \log(v+1)^2(v+2)^3=-5 \log x + c$$ via partial fractions giving $$(v+1)^2(v+2)^3=\frac{A}{x^5} \implies (y+x)^2(y+2x)^3 = A.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.